2015
DOI: 10.1038/nrn3939
|View full text |Cite
|
Sign up to set email alerts
|

The dopamine theory of addiction: 40 years of highs and lows

Abstract: Addiction has for several decades come to be viewed as a disorder of the dopamine neurotransmitter system; however, this view has not led to new treatments. We review the origins of the dopamine theory of addiction and discuss the ability of addictive drugs to elicit the release dopamine in the human striatum. There is robust evidence that stimulants increase striatal dopamine release, some evidence for alcohol, but little if any for cannabis and opiates. Moreover, there is good evidence that striatal dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
333
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 554 publications
(350 citation statements)
references
References 128 publications
11
333
1
5
Order By: Relevance
“…For psychostimulant drugs, learning drug reward associations is largely dependent on dopaminergic and glutamatergic signaling within the NAcore, whereas reinstatement is mostly driven by glutamate Koob and Volkow, 2010). However, it is important to note that additional neurochemical mechanisms are involved in drug reward associations and reinstatement of nonpsychostimulant drugs such as opiates and benzodiazepines (for review, see Badiani et al, 2011;Nutt et al, 2015).…”
Section: A Nucleus Accumbens Corementioning
confidence: 99%
“…For psychostimulant drugs, learning drug reward associations is largely dependent on dopaminergic and glutamatergic signaling within the NAcore, whereas reinstatement is mostly driven by glutamate Koob and Volkow, 2010). However, it is important to note that additional neurochemical mechanisms are involved in drug reward associations and reinstatement of nonpsychostimulant drugs such as opiates and benzodiazepines (for review, see Badiani et al, 2011;Nutt et al, 2015).…”
Section: A Nucleus Accumbens Corementioning
confidence: 99%
“…Dopamine is a neurotransmitter that is released from the neurons in the mesolimbic system and mediate emotions and pleasure (reviewed by Nutt et al 2015). It has been demonstrated that with food intake dopamine release is enhanced in the circuits that mediate the pleasurable aspects of the eating (Volkow et al 2011).…”
Section: Role Of the Reward Systemmentioning
confidence: 99%
“…Thus, 5-HT signaling is most typically associated with mood, anxiety, aggression, and appetite, with 5-HT signaling dysregulation linked to disorders such as depression, obsessive-compulsive disorder (OCD), anxiety disorders, and autism spectrum disorder (ASD) (for review, see Olivier, 2015). DA has received prominent attention for its role in circuits supporting reward, attention, and movement, with perturbed DA signaling associated with addiction, attention-deficit hyperactivity disorder (ADHD), schizophrenia, and Parkinson's disease (Viggiano et al, 2004b;Segura-Aguilar et al, 2014;Howes et al, 2015;Nutt et al, 2015 ). NE plays a prominent role in arousal, attention, executive function, and stress responses (Harley, 2004;Viggiano et al, 2004a;Morilak et al, 2005), with disorders such as ADHD, posttraumatic stress disorder.…”
mentioning
confidence: 99%